logo

Ask Questions, Get Answers

 
X
 Search
Want to ask us a question? Click here
Browse Questions
Ad
0 votes

Express the given complex number in the form $\;a+ib : (\large\frac{1}{3}$$+3i)^{3}$

$(a)\; \normalsize -\large\frac{342}{27} - \normalsize26i\qquad(b)\;\normalsize -\large\frac{242}{27} -\normalsize 26i\qquad(c)\; \normalsize -\large\frac{242}{27} -\normalsize 28i\qquad(d)\;\normalsize -\large\frac{242}{27} - \normalsize 25i$

Can you answer this question?
 
 

1 Answer

0 votes
Answer : $\;-\large\frac{242}{27} -26i$
Explanation :
$(\large\frac{1}{3}$$+3i)^{3} = (\large\frac{1}{3})^{3}+(3i)^{3}+ 3 (\large\frac{1}{3})(3i)(\large\frac{1}{3}+3i)$
$=\large\frac{1}{27}+27i^3+(3i) (\large\frac{1}{3}+3i) \qquad [i^{3} =-i]$
$=\large\frac{1}{27} +27(-i) +i+9i^2$
$= \large\frac{1}{27} -27i+i+9(-1) \qquad [i^2=-1]$
$=[\large\frac{1}{27} -9]+i(-27+1)$
$=-\large\frac{242}{27} -26i\;.$
answered Apr 9, 2014 by yamini.v
 

Related questions

Ask Question
student study plans
x
JEE MAIN, CBSE, NEET Mobile and Tablet App
The ultimate mobile app to help you crack your examinations
Get the Android App
...